Immunological Effects of Aggregation-Induced Emission Materials - Wu, Haibo; Huang, Wen; Zhou, Xingyu; Min, Yuanzeng (Frontiers in Immunology, 2020)
Nanotechnology is widely used in the fields of biology and medicine. Some special nanoparticles with good biocompatibility, hydrophilicity, and photostability can be used as ideal systems for biomedical imaging in early diagnosis and treatment of diseases. Among them, aggregation-induced emission materials are new antiaggregation-caused quenching nano-imaging materials, which have advantages in biocompatibility, imaging contrast, and light stability. Meanwhile, heterogeneity of nanoparticles may cause various adverse immune reactions. In response to the above problems, many researchers have modified nano-materials to be multifunctional nano-composites, aiming at combining diagnosis and treatment with simultaneous imaging and targeted therapy and additionally avoiding immune reactions, which is of great potential in imaging-guided therapy. This review discusses the application of aggregation-induced emission materials, and other nano-imaging materials are also mentioned. We hope to provide new ideas and methods for the imaging of nano-materials in diagnosis and treatment.